Exploring probiotics as a sustainable alternative to antimicrobial growth promoters: mechanisms and benefits in animal health - Sachdeva, Angel; Tomar, Tanu; Malik, Tabarak; Bains, Aarti; Karnwal, Arun (Frontiers in Sustainable Food Systems, 2025)
The extensive use of antimicrobial growth promoters (AGPs) in livestock has raised global concerns due to increasing antimicrobial resistance (AMR) among pathogenic microbes. This review examines probiotics as a sustainable alternative to AGPs, offering a safer approach for promoting animal growth and health. Probiotics enhance animal productivity and immunity by producing antimicrobial compounds and competing with pathogens for nutrients. In addition, probiotics strengthen the gut barrier and modulate the gut microbiome, facilitating beneficial bacterial growth while suppressing pathogenic species. Studies demonstrate the efficacy of probiotic strains of genera Lactobacillus and Bifidobacterium in inhibiting pathogens such as Clostridium perfringens and Salmonella in livestock. This comprehensive evaluation highlights probiotics' potential to advance sustainable livestock practices, reduce reliance on antibiotics, and mitigate AMR risks, underscoring the need for further research and regulatory considerations for their use in animal husbandry.